The Influence of Fashion Influencer Credibility on Purchase Intention: Examining Trustworthiness, Expertise, and Attractiveness as Credibility Dimensions - Fatullah Razi (Universitas Telkom, 2026)
This study examines the influence of fashion influencer credibility on purchase intention in Indonesia’s sustainable fashion market. Drawing on Source Credibility Theory, credibility is conceptualized through trustworthiness, expertise, and attractiveness as reflective dimensions of a single construct. Using data from 161 Instagram users and analyzed through PLS-SEM, the findings show that influencer credibility strongly predicts purchase intention (β = 0.766; R² = 0.586), with trustworthiness emerging as the most influential dimension. The study contributes to communication and marketing scholarship by confirming the applicability of credibility-based persuasion in digital sustainability contexts. Practically, the results highlight the importance of collaborating with influencers who demonstrate consistent authenticity, ethical alignment, and domain expertise to strengthen consumer intention toward sustainable fashion. Keywords: SourceCredibility Theory, Influencer Credibility, Purchase Intention, Sustainable Fashion, Digital Communication